2015
DOI: 10.1371/journal.pone.0142223
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Physical Activity in Primary School Children Using Accelerometry and Global Positioning System

Abstract: BackgroundEcological approaches have highlighted the importance of the built environment as a factor affecting physical activity. However, knowledge on children’s activity patterns is still incomplete. Particularly, data on the spatial context of physical activity is limited, which limits the potential to design location-based interventions effectively. Using global positioning system (GPS) and accelerometry, this study aimed to identify locations where children engage in moderate-vigorous physical activity (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 47 publications
0
36
0
1
Order By: Relevance
“…Burgi, 2015 45 Suisse • La proportion de temps consacré à des APMV était plus élevée dans les installations de loisirs, mais celles-ci étaient moins souvent fréquentées.…”
Section: Apmvunclassified
“…Burgi, 2015 45 Suisse • La proportion de temps consacré à des APMV était plus élevée dans les installations de loisirs, mais celles-ci étaient moins souvent fréquentées.…”
Section: Apmvunclassified
“…Looking at locations where children engaged in PA, the Winterthur authors found that boys achieve more moderate-to-vigorous physical activity (MVPA) than girls at school playgrounds, sports facilities, at recess and during the day. 15 The Denmark study pointed out that boys spend more time outdoor for MVPA than the time spent by girls. Also, half of the girls who participated in the study did not accumulate any MVPA in sports clubs and sports facilities.…”
Section: Risk Factors Of Ncds (Physical Activity/obesity)mentioning
confidence: 99%
“…1216 These technologies allow researchers to ask what types of activities at certain times, in specific locations, for various types of people matter for health outcomes. These data can be used, for instance, to test the influence of new infrastructure to affect behavior change 17,18 ; to evaluate characteristics of locations that provide opportunities for physical activity 19,20 ; or to create personalized metrics of air pollution exposure based on location and respiratory rate. 21 …”
Section: Introductionmentioning
confidence: 99%